The Development of Modified Ball Games in Stimulating the Sensorimotor Development of Children Aged 4-6 Years - Rahmawati, Siti; Ajat, Ajat (JURNAL INDRIA (Jurnal Ilmiah Pendidikan Prasekolah dan Sekolah Awal), 2025)
This study aims to develop a modified ball game to stimulate the sensorimotor development of children aged 4-6 years at Taman Bermain Sahabat Sekar Mekar, Bogor Regency. This study usResearch and Development (RD) approach with the Borg and Gall model modified into five stages, namely research and information gathering, planning, initial product development, initial field trials, and product revision. This method involves qualitative and quantitative data analysis through observations, interviews, and questionnaires conducted to teachers and experts in the fields of material and media. The results showed that the designed modified ball game successfully improved children's sensorimotor development significantly. Validation conducted by experts concluded that the game is effective in stimulating various sensorimotor aspects, such as balance, eye-hand coordination, gross and fine motor movements, and rhythmic skills. The modified ball game is also designed to be adapted to the limited space and needs of children, so that it can be applied optimally in an early childhood education environment. The limited space at Taman Bermain Sahabat Sekar Mekar, which was initially an obstacle to children's physical activity, was successfully overcome with this game modification. The trial showed that the modified ball game was able to increase children's interest and participation in physical activities as a whole.